Pengaruh Literasi Keuangan, Kontrol Diri Dan Lingkungan Teman Sebaya Terhadap Perilaku Konsumtif Mahasiswa - Kurnima; Lukmanul Hakim (Journal of Management and Business, 2021)
This study aims to examine whether there is an influence between financial literacy, self-control, and peer environment on consumptive behavior in overseas students of the Sumbawa Technology University from the 2017, 2018, 2019, and 2020. This study uses quantitative methods. The sample used in this study amounted to 91 people or respondents obtained using a probability sampling method with a simple random sampling technique. The instrument used is a questionnaire and the type of data is primary which is obtained from the results of filling out the questionnaire with a 4-point Likert scale measurement. The data obtained were processed using classical assumption testing, hypotheses and multiple linear regression analysis with the analytical tool used was SPSS. The results of this study indicate that the Financial Literacy variable has no influence on the consumptive behavior of students and the Self-Control and Peer Environment variables have an influence on the consumptive behavior of students.